2013
DOI: 10.1124/jpet.113.203471
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin Synergizes with Histone Deacetylase and DNA Methyltransferase Inhibitors in Upregulating E-cadherin Expression Together with Inhibition of Migration and Invasion of Human Non-small Cell Lung Cancer Cells

Abstract: Aggressive cancers in the epithelial-to-mesenchymal transition (EMT) phase are characterized by loss of cell adhesion, repression of E-cadherin, and increased cell mobility. Non-small cell lung cancer (NSCLC) differs in basal level of E-cadherin; predominantly exhibiting silenced expression due to epigeneticrelated modifications. Accordingly, effective treatments are needed to modulate these epigenetic events that in turn can positively regulate E-cadherin levels. Herein, we investigated silibinin, a natural f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 59 publications
0
53
0
Order By: Relevance
“…E-cadherin has important functions in regulating cell-cell interactions (25). Epigenetic silencing of E-cadherin expression was observed in advanced NSCLC, and restoration of E-cadherin expression strongly suppressed the metastasis of cancer cells (7). Vimentin is specifically expressed in normal mesenchymal cells and overexpressed in lung cancer cells (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…E-cadherin has important functions in regulating cell-cell interactions (25). Epigenetic silencing of E-cadherin expression was observed in advanced NSCLC, and restoration of E-cadherin expression strongly suppressed the metastasis of cancer cells (7). Vimentin is specifically expressed in normal mesenchymal cells and overexpressed in lung cancer cells (26).…”
Section: Discussionmentioning
confidence: 99%
“…When EMT occurs, epithelial cells gradually transform into mesenchymal-like cells by losing their epithelial-associated functions and characteristics (5). Epigenetic downregulation of E-cadherin expression was observed in advanced NSCLC and restoration of E-cadherin expression strongly suppressed the invasion/migration of tumor cells (6,7). Several signaling pathways are involved in EMT in NSCLC, including TGF-β (8), Slug (9), Wnt/β-catenin/zinc finger E-box binding homeobox 1 signaling (10) and c-Jun N-terminal kinase (JNK) signaling (11).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been shown that DNMTs are induced during EMT in several cancers, including pancreatic cancer, non-small cell lung cancer, 37 and breast cancer. 38 There are no reports available on the influence of HIF-1Îą on DNMT activity; however multiple reports are available on the interaction between HIF-1Îą and histone demethylases JMJD1A, (demethylates dimethylated histone H3 lysine 9 (H3K9Me2) and JMJD2B (demethylates trimethylated H3K9).…”
Section: Discussionmentioning
confidence: 99%
“…EMT is characterized by the loss of epithelial proteins, such as E-cadherin, and the acquisition of new mesenchymal markers, including a-smooth muscle actin (a-SMA), vimentin, and type I collagen (Col-I). It is a reversible process in which epithelial cells transform into cells with mesenchymal characteristics that contribute to ECM secretion in the progression of PF (Vittal et al, 2007;Kalluri and Weinberg, 2009;Mateen et al, 2013). Accumulated data support that injured AECs contribute greatly to the local activation of fibroblasts and myofibroblasts, and may also directly serve as a source of these cells via the EMT process (Kim et al, 2006;Liu et al, 2014;Vyas-Read et al, 2014).…”
Section: Introductionmentioning
confidence: 97%